تحليل أثر الإنفاق الحكومي الاستثماري على القدرة التنافسية للصادرات العراقية للمدة "2004-2021" - الجنابي، بهاء عبدالوهاب عبدالحسين; الجبوري، سوسن كريم هودان (الجمعية العلمية للدراسات التربوية المستدامة, 2024)
تمارس متغيرات السياسة المالية وبالأخص الأنفاق الحكومي الاستثماري؛ أثرا واضحا على جميع القطاعات الاقتصادية، وبالتالي بالإمكان تحقيق فائض في الميزان التجاري من خلال توجيه الأنفاق الحكومي الاستثماري صوب القطاعات الإنتاجية غير الريعية، من أجل زيادة معدلات التبادلات التجارية مع العالم الخارجي وبما يعزز من القدرة التنافسية للبلد، وبالتالي زيادة حجم الصادرات إلى الأسواق العالمية. ولذلك جاء هذا البحث ليركز على أثر الأنفاق الحكومي الاستثماري على القدرة التنافسية للصادرات العراقية، إذ تناول البحث تأصيل نظري وتحليلي للإنفاق الحكومي والقدرة التنافسية. وتأتي أهمية البحث بتناوله مسألة التنافسية والتوظيف الفاعل للإنفاق الحكومي الاستثماري من أجل تحقيق تنافسية القطاع التجاري المتمثل بالصادرات، أما مشكلة البحث فقد تمثلت بالتساؤل التالي: كيف يمكن للاقتصاد العراقي من تحقيق التنافس التجاري في صادراته في ضوء شروط عمليات التبادل التجاري للتكتلات الاقتصادية الدولية. وانطلق البحث من فرضية مفادها أن للإنفاق الحكومي الاستثماري تأثير قوي في تحقيق القدرة التنافسية للقطاع التجاري لاقتصاد العراق للمدة (۲۰۰٤ -۲۰۲۱)، وقد توصل البحث إلى مجموعة من الاستنتاجات نذكر بعض منها، توجد علاقة طردية بين النفقات الاستثمارية التي تمثل المتغير المستقل وبين المتغير التابع وهو الصادرات، وأيضا هيمنة قطاع الأنفاق الحكومي الجاري (التشغيلي) بنسبة كبيرة على مكونات الأنفاق الحكومي الإجمالي، ويتضح أيضا عدم التوازن بين التخصيصات المالية المخصصة للنفقات الاستثمارية والنفقات التشغيلية واستحواذ التشغيلية على النسبة الأكبر، أما التوصيات فقد تمثلت بضرورة التنويع الاقتصادي، وتطوير القطاعات الاقتصادية غير النفطية، وأيضا ضرورة التنسيق وتحقيق التوازن في التخصيصات المالية عند إعداد الموازنات العامة، وزيادة نسبة النفقات الاستثمارية، وضرورة تشجيع بعض المنتجات التي يمتلك فيها العراق ميزة تنافسية سواء من ناحية الأسعار أو جودة المنتج، وذلك من خلال تقديم الدعم المالي لتلك المنتجات في المراحل الأولى لها من العملية الإنتاجية بهدف تطويرها وتنميتها لتصبح من السلع المنافسة للمنتجات الأجنبية مستقبلا. Fiscal policy variables, especially government investment spending, have a clear impact on all economic sectors, and therefore it is possible to achieve a surplus in the trade balance by directing government investment spending towards non-rentier productive sectors in order to increase the rates of trade exchanges with the outside world and in a way that enhances the country’s competitiveness and thus increases The volume of exports to global markets. Therefore, this research came to focus on the impact of government investment spending on the competitiveness of Iraqi exports, as the research dealt with a theoretical foundation of government spending and competitiveness. The importance of the research comes in addressing the issue of competitiveness and effective use of government investment spending in order to achieve competitiveness in the commercial sector represented by exports. The problem of the research was represented by the following question: How can the Iraqi economy achieve commercial competitiveness in its exports in light of the conditions of trade exchange operations of international economic blocs. The research started from the research hypothesis that government investment spending has a strong impact on achieving the competitiveness of the commercial sector of the Iraqi economy for the period (2004- 2021), and the research reached a set of conclusions, some of which we mention: There is a direct relationship between investment expenditures, which represent the independent variable, and the dependent variable, which is exports. Also, the dominance of the current government expenditure sector (operating) by a large percentage over the components of total government expenditure is also evident. It is also clear that there is an imbalance between the financial allocations allocated to investment expenditures and operational expenditures, with operational taking over the largest proportion. The recommendations included the necessity of economic diversification and the development of non-oil economic sectors, as well as the necessity of coordination and achieving balance in financial allocations when preparing public budgets and increasing the proportion of investment expenditures, and the necessity of encouraging some products in which Iraq has a competitive advantage, whether in terms of prices or product quality, through Providing financial support for these products in their early stages of the production process with the aim of developing them and growing them to become competitive goods for foreign products in the future.
Keywords: السياسات المالية -- النفقات الاستثمارية -- الميزات التنافسية -- الصادرات العراقية